Development of ‘Mabini’ jackfruit (Artocarpus heterophyllus Lamk.), a dual-purpose variety (2010)
On-site selection and evaluation of Jackfruit (Artocarpus heterophyllus Lamk.) trees grown from seeds in Laguna, Batangas and Cavite, Philippines were conducted to identify superior individual trees for variety release and registration. The best selection was identified out of 100 individual trees evaluated preliminary for various horticultural characteristics. After another two succeeding evaluation periods, this selection was found consistent in terms of organoleptic traits particularly flesh sweetness, total soluble solids, flesh texture, flesh color, aroma, and yield. This selection was proven outstanding in terms of fruit qualities both as fresh and processing type. The selection was released as a variety called ‘Mabini’, named after the national hero, Apolinario Mabini, a sublime paralytic who once lived in Talaga, Tanauan City, Batangas, the place where the original jackfruit tree was selected in 2000. ‘Mabini’ is a dual-purpose jackfruit variety with unknown parentage registered with the National Seed Industry Council. The fruit is oblong, weighs 15,433.33 g and measure 451.67 mm long and 290.67 mm wide. The skin and and spines are yellow green (RHS 1-B) when ripe, rough textured and thick (11.63 mm). The fruitlet is big (32.70 g) while the flesh is bright yellow orange (RHS 23-A), juicy, smooth, semi-crispy, has strong aroma, moderate latex, no fibers, thick (5.97 mm) and sweet (20.40 Bx). The whole fruit has a medium-sized core (1,100 g) with a diameter of 98.33 mm and relatively large edible portion (50.20%). The seed is oblong with grey-orange (RHS 165-D) testa, weighs 5.27 g, and measures 34.21 mm long and 21.07 mm wide. The tree is 7m tall, vigorous, evergreen, has semi-spreading growth habit, a regular bearer yielding 50-80 mature and marketable fruits per season, with a peak fruiting season from February to July.